Effect of Self Management Education on Knowledge and Self Efficacy of pulmonary TB Clients in Timor Tribal Community - Muhammad Saleh Nuwa; Stefanus Mendes Kiik (STIKes Patria Husada Blitar, 2021)
Background: Pulmonary Tuberculosis (TB) disease is still the main cause of death among the poor with low knowledge. Knowledge and self efficacy are the keys to the successful management of pulmonary TB. Objective: The purpose of this study was to investigate the effect of self management education (SME) by emphasizing the five pillars of TB management on knowledge and self efficacy of pulmonary TB clients in the Timor tribal community in Kupang, Indonesia. Methods: This quasi experimental study was conducted on 30 primary pulmonary tuberculosis patients who undergoing treatment for 6 months. The research was conducted from January to October 2020 in the working area of the Naibonat Community Health Center, Kupang Regency. Data were collected using a questionnaire on demographic data, knowledge and self efficacy which had been tested for validity and reliability.. Data were analyzed by the Paired T-test with SPSS 21. Results: The mean score of pre test knowledge and self efficacy of clients with pulmonary TB, respectively, 5.23 ± 1.04 and 4.77 ± 1.07 increased significantly to 6, 33 ± 1.18, and 7.13 ± 0.94 on the post test (P <0.001). Conclusion and recommendation: giving SME by emphasizing the five pillars of pulmonary TB management increases the knowledge and self-efficacy of pulmonary TB clients in the Timor tribal community. The recommendation of this study is that SME interventions can be used as one of the nursing interventions in the public health center in community empowerment based pulmonary TB management